China’s Population Aging, Human Capital and Economic Growth -Comparison with the United States, Japan, and Korea - Zhu, Mingliang; Zhang, Tiegang (International Journal of English Literature and Social Sciences (IJELS), 2019)
This paper focuses on the status quo of China's population aging , that is, the current Chinese society is faced with the characteristics of aging: (1) the age structure of the labor force is aging, and there is a tendency to catch up with Japan and South Korea ; (2) the old-age dependency ratio and the child-rearing ratio rise simultaneously that brings double pressure to society ; (3) China's process of enrichment in the old process is also accelerating ; (4) The rapid rise of aging is slowly coming. At the same time, the related researches on the aging of the population in this field are discussed, and the relationship between population aging and human capital is complicated. The aging of the population affects the human capital transmission on economic growth, positive for economic growth or negative. At the same time, this paper compares the status quo of China's population aging with the three typical aging countries: the United States, Japan, and Korea.